THE INFLUENCES OF BRAND AMBASSADOR AND BRAND AWARENESS ON CONSUMER PURCHASE DECISION OF NATURE REPUBLIC SKINCARE IN MANADO - Michelle Awuy; Stans Joyce Lapian; Shinta Wangke (Universitas Sam Ratulangi, 2024)
This study aims to test whether Brand Ambassadors and Brand Awareness have a significant effect on purchasing decisions for Nature Republic skincare products. The subject of this study focuses on how the Gen-Z in Manado responds to this specific matter. This research type is causal which uses a quantitative type of research. This research used the multiple linear regression analysis method and SPSS as an analysis tool. The data source used is primary, where the data is collected through questionnaire with a total of 106 respondents among Gen Z in Manado who has known Nature Republic. The results of the first hypothesis are rejected, indicating that Brand Ambassador does not influence Gen Z's purchase decision regarding Nature Republic. Accepting the results for the second hypothesis signifies that brand awareness plays a favorable and constructive role in influencing Gen Z's purchase decisions regarding Nature Republic. The rejection of the third hypothesis indicates that, contrary to expectations, brand ambassador and brand awareness are not concurrently exerting a joint influence on the purchase decisions of Nature Republic, which aligns with the earlier rejected hypothesis. Keyword: Marketing, Brand Ambassador, Brand Awareness, Purchase Decisions